Targeting the alpha subunit of IL-3 receptor (CD123) in patients with acute leukemia - Ibrahim Aldoss; Mary Clark; Joo Y Song; Vinod Pullarkat (Human Vaccines & Immunotherapeutics, 2020)
The IL-3 alpha chain receptor (CD123) is a cell surface protein that is widely expressed by various subtypes of acute leukemia, including acute myeloid leukemia (AML), acute lymphoblastic leukemia and blastic plasmacytoid dendritic cell neoplasm. Notably, CD123 is preferentially overexpressed in leukemia stem cells (LSC) in contrast to normal hematopoietic stem cells, and this differential expression allows for the selective eradication of LSC and leukemic blasts through therapeutic targeting of CD123, with less impact on hematopoietic cells. The level of CD123 expression in AML correlates with both treatment response and outcomes. Therefore, targeting CD123 represents a promising universal therapeutic target in advanced acute leukemias irrespective of the individual leukemia phenotype. There are currently 31 ongoing clinical trials examining the utility of CD123-based targeted therapies. Here we focus our review on current efforts to target CD123 in acute leukemia through various therapeutic constructs.